2002
DOI: 10.1161/01.hyp.0000030178.90322.11
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamic and Natriuretic Effects of Concomitant Angiotensin-Converting Enzyme and Neutral Endopeptidase Inhibition in Men

Abstract: Abstract-This double-blind placebo-controlled study was designed to investigate the acute and sustained hormonal, renal hemodynamic, and tubular effects of concomitant ACE and neutral endopeptidase (NEP) inhibition by omapatrilat, a vasopeptidase inhibitor, in men. Thirty-two normotensive subjects were randomized to receive a placebo, omapatrilat (40 or 80 mg), or the fosinopril/hydrochlorothiazide (FOS/HCTZ; 20 and 12.5 mg, respectively) fixed combination for 1 week. Blood pressure, renal hemodynamics, urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
4
22
1
Order By: Relevance
“…Augmentation of bradykinin-mediated vasodilatation within the kidney may also contribute to the greater increase in renal blood flow observed with combined ACE and NEP inhibition than ACE inhibition alone. 38 As a result, it has been suggested that combined ACE and NEP inhibition may afford greater renal protection than ACE inhibition alone. 38 However, it should be noted that potentiating the vascular actions of kinins may have detrimental effects.…”
Section: Cruden Et Al Neutral Endopeptidase Inhibition and Bradykininmentioning
confidence: 99%
See 1 more Smart Citation
“…Augmentation of bradykinin-mediated vasodilatation within the kidney may also contribute to the greater increase in renal blood flow observed with combined ACE and NEP inhibition than ACE inhibition alone. 38 As a result, it has been suggested that combined ACE and NEP inhibition may afford greater renal protection than ACE inhibition alone. 38 However, it should be noted that potentiating the vascular actions of kinins may have detrimental effects.…”
Section: Cruden Et Al Neutral Endopeptidase Inhibition and Bradykininmentioning
confidence: 99%
“…38 As a result, it has been suggested that combined ACE and NEP inhibition may afford greater renal protection than ACE inhibition alone. 38 However, it should be noted that potentiating the vascular actions of kinins may have detrimental effects. Bradykinin has been implicated in the pathogenesis of ACE inhibitor-mediated angioedema.…”
Section: Cruden Et Al Neutral Endopeptidase Inhibition and Bradykininmentioning
confidence: 99%
“…68 Omapatrilat (40 mg and 80 mg) was also compared with fosinopril/hydrochlorothiazide combination (20 mg and 12.5 mg) in normotensive subjects. 69 Although the acute natriuretic effects of the fosinopril/hydrochlorothiazide combination were higher, the cumulative sodium excretion was similar for omapatrilat and the fosinopril/hydrochlorothiazide combination over 7 days. Omapatrilat, but not the fosinopril/hydrochlorothiazide combination, produced a marked increase in renal plasma flow, indicative of renal vasodilatation, without change in GFR.…”
Section: Evaluation Of Vasopeptidase Inhibitors In Humans Normotensivmentioning
confidence: 89%
“…Omapatrilat, but not the fosinopril/hydrochlorothiazide combination, produced a marked increase in renal plasma flow, indicative of renal vasodilatation, without change in GFR. 69 …”
Section: Evaluation Of Vasopeptidase Inhibitors In Humans Normotensivmentioning
confidence: 99%
“…Interestingly, preliminary studies conducted with omapatrilat failed to demonstrate significant changes in urinary sodium excretion, suggesting that the drug is not functioning primarily as an ACE inhibitor-diuretic combination. More recent studies, however, have demonstrated that omapatrilat indeed increases renal sodium excretion [16,17]. Over 1 week, the natriuretic properties of omapatrilat were comparable to the natriuretic effects of an ACE-hydrochlorothiazide fixed combination [16].…”
Section: Preclinical and Preliminary Clinical Studiesmentioning
confidence: 97%